The Protective Effect of Amifostine on Radiation-Induced Proctitis: Systemic Versus Topical Application - Cem Uzal; Atakan Sezer; Ufuk Usta; Necdet Süt; Alaattin Özen; Mehmet Ali Yağcı (Balkan Medical Journal, 2012)
Objective: The aim of the study was to evaluate the radioprotective efficacy of intrarectal administration of amifostine in radiation-induced proctitis compared to intraperitoneal administration.Materials and Methods: Thirty-two Sprague-Dawley rats were randomly divided into four groups: Control (CONT), irradiation alone (RT), intraperitoneal amifostine plus irradiation (IPAMI), and intrarectal amifostine plus irradiation (IRAMI). The rats in the RT, IPAMI and IRAMI groups were irradiated individually with a single dose of 17.5 Gy to the pelvis. Amifostine was administered by the intraperitoneal (200 mg/kg) or intrarectal (2000 mg/kg) route before irradiation. Histopathologic analysis of the rectum was performed 14 days after irradiation. Results: Significant radiation damage appeared in all histopathologic parameters and was reduced by amifostine. Pretreatment with IPAMI significantly reduced the inflammatory infiltrate in the lamina propria (p=0.021), cryptitis (p=0.002) and crypt abscess (p=0.015). However, the protective effect of IRAMI was significant for all parameters with equal or higher significance than IPAMI, including the eosinophil leucocytes count (p=0.02), and distortion of the crypts (p=0.008), and was also significant for regenerative/reparative atypia (p=0.013). Conclusion: Intrarectal high dose topical administration of amifostine is more effective in the prevention of radiation-induced proctitis compared to its intraperitoneal systemic administration.